(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the linguocultural features of toponym translation in the English versions of Baburnama. It analyzes the main translation strategies used in rendering toponyms, including transliteration, semantic translation, explanatory translation, and their combined forms. The study also investigates differences between the Leyden–Erskine and V. Texton translations, focusing on pragmatic adequacy and the degree of cultural meaning preservation. The analysis demonstrates that toponyms function not only as linguistic units but also as linguocultural elements that encode national and cultural information. The findings show that transliteration is effective in preserving national specificity, while explanatory translation improves reader comprehension. However, neither approach fully ensures complete linguocultural equivalence in translation.